2017
DOI: 10.1213/ane.0000000000001801
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Deep Versus Moderate Neuromuscular Block on Surgical Conditions and Postoperative Respiratory Function in Bariatric Laparoscopic Surgery: A Randomized, Double Blind Clinical Trial

Abstract: Compared with a moderate NMB, there was insufficient evidence to conclude that deep NMB improves surgical conditions during laparoscopic bariatric surgery. Postoperative pulmonary function was substantially decreased after laparoscopic bariatric surgery independently of the NMB regime that was used. The study is limited by a small sample size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 25 publications
0
30
0
1
Order By: Relevance
“…The study showed an improvement of 0.7 L-SRS points (mean L-SRS 4.0 versus 4.7) when deep NMB was applied, an improvement deemed clinically significant by the surgical team 19 . In many other procedures, a similar effect of deep NMB was found 18 , 20 , 21 , 52 54 , but it is important to acknowledge that some studies found no effect of deep NMB on surgical conditions (see Table 2 ) 55 . A recent meta-analysis confirmed the positive effect of a deep NMB on surgical conditions and reduced postoperative pain scores; however, significant heterogeneity between the included studies reduces the overall quality of evidence 56 .…”
Section: Deep Neuromuscular Block: Prevention Of Diaphragmatic Contramentioning
confidence: 57%
“…The study showed an improvement of 0.7 L-SRS points (mean L-SRS 4.0 versus 4.7) when deep NMB was applied, an improvement deemed clinically significant by the surgical team 19 . In many other procedures, a similar effect of deep NMB was found 18 , 20 , 21 , 52 54 , but it is important to acknowledge that some studies found no effect of deep NMB on surgical conditions (see Table 2 ) 55 . A recent meta-analysis confirmed the positive effect of a deep NMB on surgical conditions and reduced postoperative pain scores; however, significant heterogeneity between the included studies reduces the overall quality of evidence 56 .…”
Section: Deep Neuromuscular Block: Prevention Of Diaphragmatic Contramentioning
confidence: 57%
“…condTorensma [4]2016Bariatric surgeryDeep versus moderate NMB5 point a 1 (extremely poor)–5 (optimal)310 minMean SRS, % subopt./opt. condBaete [5]2017Bariatric surgeryDeep versus moderate NMB5 point a 1 (extremely poor)–5 (optimal)1End of surgeryMean SRSCaldwell [24]1985GynaecologyNMB3 point1 (good)–3 (inadequate)UnknownUnknownSRS distributionWilliams [16]2003GynaecologyModerate versus no NMB4 point1 (poor)–4 (excellent)UnknownUnknownSRS distributionDubois [2]2014GynaecologyDeep versus moderate NMB4 point1 (optimal)–4 (unacceptable)110 minMean SRS, SRS distributionMadsen [15]2015GynaecologyDeep versus no NMB4 point1 (optimal)–4 (bad)2Fascia closureMean SRS, intra-abdominal space (cm)Taylor [19]1992General surgeryNitrous oxide5 point1 (extremely poor)–5 (very good)115 minSRS, bowel distentionStaer Rye [20]2014General surgeryDeep versus moderate NMB…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it is in line with the ongoing controversial debate on neuromuscular blockade to improve surgical conditions. Whereas many publications present significantly better operating conditions during deep NMB, compared to a light block [3,4,8,14,[17][18][19], several other authors found no differences [1,15,20]. Park et al describe inconsistent results and state that "further studies are required to address the heterogeneity and power shortage demonstrated by the trial sequential analysis", in a previously published review [21].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies examined the influence of the neuromuscular block (NMB) on the quality of operating conditions [1][2][3][4][5][6][7][8][9][10]. Therefore, intraabdominal measurements, e.g., of abdominal volume, were performed [2,5,6], and several scores were developed [4,8,11].…”
Section: Introductionmentioning
confidence: 99%